DS8870 data migration techniques - Warmuth, Alexander; Dufrasne, Bertrand; Appel, Joachim; Bauer, Werner; Douglass, Susan; Klee, Peter; Pura, Miroslaw; Wells, Mark; Wesselbaum, Bjoern (IBM Corporation, Interantional Technical Support Organization, 2015)
This IBM® Redbooks® publication describes data migrations between IBM DS8000® storage systems, where in most cases one or more older DS8000 models are being replaced by the newer DS8870 model. Most of the migration methods are based on the DS8000 Copy Services. The book includes considerations for solutions such as IBM Tivoli® Productivity Center for Replication and the IBM Geographically Dispersed Parallel Sysplex™ (GDPS®) used in IBM z/OS® environments. Both offerings are primarily designed to enable a disaster recovery using DS8000 Copy Services. In most data migration cases, Tivoli Productivity Center for Replication or GDPS will not directly provide functions for the data migration itself. However, this book explains how to bring the new migrated environment back into the control of GDPS or Tivoli Productivity Center for Replication. In addition to the Copy Services based migrations, the book also covers host-based mirroring techniques, using IBM Transparent Data Migration Facility (TDMF®) for z/OS and the z/OS Dataset Mobility Facility (zDMF).
Number from resource description page: SG24825700. - Includes footnotes, related publications with bibliographical references to other IBM® Redbooks®. - Description based on online resource; title from title page (Safari, viewed May 21, 2015)
Keywords: Computer architecture; Storage area networks (Computer networks); Ordinateurs; Architecture; Réseaux de stockage (Informatique)